THE INFLUENCE OF LEARNING STYLES ON THE LANGUAGE ABILITY OF KINDERGARTEN CHILDREN - Azizah Amal; Andi Sriwahyuni Asti; St. Nurhidayah Ilyas (Universitas Negeri Makassar, 2023)
This research is a experimental research that aims to know: the interaction effect between REA and learning style on language ability. The population in this research is all kindergarten children in Makassar City. The research sample was done by random technique and kindergarten that was chosen there are two kindergarten that is TK Teratai UNM that consists of 20 people and Rahma Kindergarten with 20 children. This research analysis the findings using descriptive analysis techniques and inferential test analysis. The result of this research show that language ability of children who have a field dependent learning style is higher than children who have field independent. So based on this explanation, improving language skills in children requires paying attention to the child’s learning style so that the learning activities provided are appropriate and able to stimulate the child’s development, it must be considered factor learning style of children.